The Paradigm of Pluralism In Indonesia: Communal VS Legal State - Flambonita, Suci; Novianti, Vera; Febriansyah, Artha; Ernaningsih, Wahyu (Technium Social Sciences Journal, 2021)
Indonesia with all of its diversities in which law and culture live side by side and become part of state law regularity. Centralistic view contends that the only institution which plays role in creating social regularity is the country through the law formed and determined by the country. In its reality, there are many ‘other forces’ that do not come from the state such as customary law, religion law, habits, trade agreement across country and so on. Those forces also have the ability to regulate the community actions bound in it even sometimes the member or the community in the society prefers to obey the rules formed by their group compared to the state law regulations. The research method used was sociological approach with moral, ethic, and religious approach. Traditional communities are groups of individuals who live from generation to generation in a certain geographical territory and are bind by cultural identities, strong relationships with their indigenous land, regions, and natural resources. Their value system determines their economic, political, and legal institutions. Indigenous peoples are groups of individuals who live from generation to generation in a certain geographical territory and are bind by cultural identities, strong relationships with their indigenous land, regions, and natural resources. Their value system determines their economic, political, and legal institutions arranged by customary institutions that have the authority to govern.